Analiza vloge dejavnikov, ki vplivajo na izbiro poklicne poti - Pavlin, Samo (Teorija in praksa, 2007)
The article analyses the ways how various experiences with educational system,personal interests, material factors, friends and parents impact the choice of educational programme and vocational path. It is established that the impact of material factors decreases and the role of personal interests increases with the higher level of education. We further analysed how the stated factors influence the reality of vocational ideas, which consequently after the education leads to better results and working effectiveness. We found out that the stronger the influence of, on the first sight diametrical factors, personal interest and material factor, the better the reality of vocational ideas. In addition we show that besides the stated factors of educational programme choice, there is noted the influence of "external elements of vocational professionalisation rather than the influence of the nature of vocational work itself. This represents a special problem at the new and rapidly changing vocations, especially in the field of natural science and mechanics.
Keywords: Occupational choice; Poklicna izbira; Education; Izobraževanje; Occupations; Poklici; izbira poklica; poklicno svetovanje; analiza